Pengaruh Pola As Uh Orang Tua Terhadap Kemandirian Belajar Siswa Kelas IV SDN Gugus 01 Seteluk Tahun Ajaran 2020/2021 - Resiana Resiana; Lalu Hamdian Affandi; Heri Setiawan (Journal of Science Instruction and Technology, 2021)
This study aimed to determine the influence of parents’ parenting system on the independence of students in grade IV SDN Gugus 01 Seteluk Period 2020/2021. This study uses a quantitative approach with a type of ex post facto research. The samples used in this study were 82 students from 155 populations, where sampling techniques use proportional random sampling techniques. Data collection method using questionnaire method (questioner). The data analysis technology used to test hypotheses is a non-parametric statistical test using the Kruskal-Wallis test technique assisted by the SPSS 16.0 for Windows program. The results showed that the average level of independence of students was at a high level, while for parenting patterns showed that the number of students who chose authoritarian parenting patterns as many as 16, who chose permissive foster care patterns as many as 7, and who chose democratic parenting patterns as many as 59. The data analysis result obtained asymp.sig value of 0.000 or < 0.05 then "Ho rejected" and "Ha accepted". it can be said that there is a difference in the level of student learning independence between students who use authoritarian, permissive, and democratic parenting patterns. Because of the significant differences, it is said that "there is an influence of parenting patterns on the learning independence of grade IV students of Cluster 01.